A novel molecular magnetic resonance imaging agent targeting activated leukocyte cell adhesion molecule as demonstrated in mouse brain metastasis models. Issue 7 (July 2021) - Zarghami, Niloufar; Soto, Manuel Sarmiento; Perez-Balderas, Francisco; Khrapitchev, Alexandre A; Karali, Christina Simoglou; Johanssen, Vanessa A; Ansorge, Olaf; Larkin, James R; Sibson, Nicola R
Molecular magnetic resonance imaging (MRI) allows visualization of biological processes at the molecular level. Upregulation of endothelial ALCAM (activated leukocyte cell adhesion molecule) is a key element for leukocyte recruitment in neurological disease. The aim of this study, therefore, was to develop a novel molecular MRI contrast agent, by conjugating anti-ALCAM antibodies to microparticles of iron oxide (MPIO), for detection of endothelial ALCAM expression in vivo . Binding specificity of ALCAM-MPIO was demonstrated in vitro under static and flow conditions. Subsequently, in a proof-of-concept study, mouse models of brain metastasis were induced by intracardial injection of brain-tropic human breast carcinoma, lung adenocarcinoma or melanoma cells to upregulate endothelial ALCAM. At selected time-points, mice were injected intravenously with ALCAM-MPIO, and ALCAM-MPIO induced hypointensities were observed on T2 *-weighted images in all three models. Post-gadolinium MRI confirmed an intact blood-brain barrier, indicating endoluminal binding. Correlation between endothelial ALCAM expression and ALCAM-MPIO binding was confirmed histologically. Statistical analysis indicated high sensitivity (80–90%) and specificity (79–83%) for detection of endothelial ALCAM in vivo with ALCAM-MPIO. Given reports of endothelial ALCAM upregulation in numerous neurological diseases, this advance in our ability to image ALCAM in vivo may yield substantial improvements for both diagnosis and targeted therapy.